COOPERATION AMONG COOPERATIVES AS AN INTER-COOPERATIVE LEARNING CAPABILITY: EVIDENCE FROM CROSS-CASE SYNTHESIS - Issa G Ahmed; Hussein H Laizer; Emmanuel A Gwao (Universitas Nusa Cendana, 2026)
This article reframes Principle 6 as an inter-cooperative learning capability and synthesizes how cooperation architectures convert solidarity into measurable economic and social value. Using secondary data, the study integrates a structured review of cooperative identity and policy guidance with cross-case synthesis of six widely documented cooperation models; evidence was triangulated from ICA, ILO, UN, the World Cooperative Monitor 2025, and publicly available organizational reports. Five recurring learning pathways emerge: purchasing and shared services; benchmarking and peer advisory systems; federation-enabled standard setting; joint ventures and platform cooperation; and capability building through training and mentorship. Pathways perform best when governance preserves member autonomy, uses transparent redistribution, and institutionalizes learning roles. Cooperation among cooperatives operates as a learn-and-scale system that strengthens governance, innovation, resilience, and SDG delivery. Limitation: reliance on secondary, publicly available evidence. Subsequent research should test the Inter-Cooperative Learning Capability framework with primary and longitudinal data. Keywords: Capability Building; Cooperative Networks; Inter-Cooperation; Organizational Learning; Resilience